A Comparison of Metacognitive Therapy in Current Versus Persistent Depressive Disorder – A Pilot Outpatient Study - Winter, Lotta; Gottschalk, Julia; Nielsen, Janina; Wells, Adrian; Schweiger, Ulrich; Kahl, Kai G. (Frontiers in Psychology, 2019)
Background: Metacognitive therapy (MCT) is a modern approach with demonstrated efficacy in current major depressive disorder (MDD). The treatment aims to modify thinking styles of rumination and worry and their underlying metacognitions, which have been shown to be involved in the initiation and perpetuation of MDD. We hypothesized that metacognitive therapy may also be effective in treating persistent depressive disorder (PDD). Methods: Thirty depressed patients (15 with MDD; 15 with PDD) were included. Patients in both groups were comparable on depression severity and sociodemographic characteristics, but PDD was associated with more former treatments. Metacognitive therapy was applied by trained psychotherapists for a mean of 16 weeks. Results: We observed a significant improvement of depressive symptoms in both groups, and comparable remission rates at the end of treatment and after 6 months follow-up. Furthermore, we observed significant and similar levels of improvement in rumination, dysfunctional metacognitions and anxiety symptoms in both groups. Limitations: The study is limited by the small sample size and a missing independent control group. The effect of the therapeutic alliance was not controlled. The quality of depression rating could have been higher. Conclusions: We demonstrated that metacognitive therapy can successfully be applied to patients with PDD. The observed results were comparable to those obtained for patients with current major depressive disorder. Further studies with larger groups and a randomized design are needed to confirm these promising initial findings.